Rapid Atlantification along the Fram Strait at the beginning of the 20th century - Tesi, Tommaso; Muschitiello, Francesco; Mollenhauer, Gesine; Miserocchi, Stefano; Langone, Leonardo; Ceccarelli, Chiara; Panieri, Giuliana; Chiggiato, Jacopo; Nogarotto, Alessio; Hefter, Jens; Ingrosso, Gianmarco; Giglio, Federico; et al. (Science Advances, 2021)
The recent expansion of Atlantic waters into the Arctic Ocean represents undisputable evidence of the rapid changes occurring in this region. Understanding the past variability of this “Atlantification” is thus crucial in providing a longer perspective on the modern Arctic changes. Here, we reconstruct the history of Atlantification along the eastern Fram Strait during the past 800 years using precisely dated paleoceanographic records based on organic biomarkers and benthic foraminiferal data. Our results show rapid changes in water mass properties that com-menced in the early 20th century—several decades before the documented Atlantification by instrumental records. Comparison with regional records suggests a poleward expansion of subtropical waters since the end of the Little Ice Age in response to a rapid hydrographic reorganization in the North Atlantic. Understanding of this mechanism will require further investigations using climate model simulations